2019
DOI: 10.36787/jsi.v2i1.49
|View full text |Cite
|
Sign up to set email alerts
|

Implementasi Model Cooperative Learning Teknik Stad Untuk Meningkatkan Kemampuan Berpikir Kreatif Mengajar dalam Program Latihan Profesi

Abstract: Pembelajaran tampilan nyata dimana praktek bagi calon tenaga pengajar, tidak terbentuk secara otomatis dan instan, akan tetapi didukung dengan berbagai faktor; diantaranya kondisi lapangan, penguasaan materi, metoda, model, teknik, taktik dan didukung oleh media, alat, sumber yang relevan dan dapat memberikan alternative penyeleaian secara Constructive, Supportive, kesiapan mental, keterampilan dan kemampuan Performance untuk menunjang bekal program pelatihan profesi. Tujuan Penelitian, untuk menemukan perbeda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 0 publications
0
4
0
3
Order By: Relevance
“…For a teacher who is still a beginner in implementing cooperative learning, it would be better to use this method because the steps are still simple and do not take too long (Alman, 2017;Hijrihani & Wutsqa, 2015). The STAD Cooperative Learning Model is a cooperative learning approach that is active in activities and interactions among students to motivate and assist each other in mastering subject matter to achieve maximum achievement (Anggraini et al, 2018;Suherti & Tsuroya, 2019;Zahro et al, 2018a). Teachers who use STAD submit new academic information to students every week using verbal or text presentations (Jubaedah, 2017;Laksono et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…For a teacher who is still a beginner in implementing cooperative learning, it would be better to use this method because the steps are still simple and do not take too long (Alman, 2017;Hijrihani & Wutsqa, 2015). The STAD Cooperative Learning Model is a cooperative learning approach that is active in activities and interactions among students to motivate and assist each other in mastering subject matter to achieve maximum achievement (Anggraini et al, 2018;Suherti & Tsuroya, 2019;Zahro et al, 2018a). Teachers who use STAD submit new academic information to students every week using verbal or text presentations (Jubaedah, 2017;Laksono et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Temuan penelitian sebelumnya menyatakan bahwa kegiatan pembelajaran yang membuat siswa memperoleh pengalaman langsung dalam memecahkan masalah tentu akan meningkatkan pemahaman siswa sehingga berdampak pada hasil belajar siswa yang meningkat (Stover et al, 2016;Yang et al, 2018). Temuan lainnya juga menyatakan bahwa perpaduan model dan media yang sesuai menyebabkan siswa menjadi lebih aktif dalam pembelajaran dan akan menciptakan suasana pembelajaran yang berbeda dari sebelumnya (Anggraini et al, 2019;Suherti & Tsuroya, 2019;Utama et al, 2014). Penelitian lainnya juga menyatakan bahwa penggunaan media Fun Thinkers ini dapat membantu proses pembelajaran menjadi lebih lancar dan tentu berdampak pada tujuan pembelajaran yang akan tercapai maksimal (Jummita et al, 2021;Kibtiah et al, 2021).…”
Section: Pembahasanunclassified
“…Therefore, it can also be concluded that the higher a person's physical and mental activity, the better his learning activities will be. On the other hand, people say they are studying but physical and mental activities, which means learning activities do not understand well that they are participating in learning activities (Mustakim, 2020;Rahmayani et al, 2019;Suherti & Tsuroya, 2019). Learning media such as videos can make students understand learning correctly (Alfianti et al, 2020;Maryanti & Kurniawan, 2018).…”
Section: Dicussionmentioning
confidence: 99%